Computers, Literature and Philology CLiP 2003 - Nicolas Martinez, Carlota (Firenze University Press, 2005)
The book presents the proceedings of the international conference CLiP 2003, Computer Literacy and Philology, held in Florence on 4 and 5 December 2003 within the framework of the celebrations for the 80th anniversary of Florence University. The aim of the conference was to integrate humanistic disciplines with ICT technologies, and the publication is oriented to issues related to multilingualism. The contributions illustrate different types of IT tools now available to facilitate access to and management and study of the cultural heritage, more specifically that aspect of the heritage with which philologists and linguists are typically concerned.